Restoration of highly mutilated endodontically treated multi-rooted teeth using customized interlocking post & core : A case report - Jain, Ajay; Bhat, Vinaya; Sridevi, Ugrappa (Journal of Health and Allied Sciences NU, 2015)
An endodontically treated teeth should have a good prognosis. It can resume full function and serve satisfactorily as an abutment for a fixed dental prosthesis (FDP) or a removable partial dental prosthesis. However, special techniques are needed to restore such a tooth. There are various techniques of post and core advocated in the literature. This case report presents the restoration of highly mutilated endodontically treated multi-rooted teeth using customized interlocking post and core technique.
Keywords: Post and core; multirooted; interlocking; mutilated tooth; endodontic